Analysis of the Influence of Ayureira’s Influencer Content Strategy on Brand Awareness of Body Care Products Among Generation Z in Sidrap Regency - Okta Rosita Nugrahadini Kumala; A. Rio Makkulau Wahyu; Rusnaena Rusnaena; Arwin Arwin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study investigates the effect of local influencers’ content strategies on brand awareness of body care products among Generation Z consumers in Sidenreng Rappang Regency, Indonesia. The increasing use of social media as a marketing platform and the growing influence of local content creators have transformed the way consumers perceive and recognize brands, particularly in the beauty and personal care industry. Using a quantitative research design, data were collected from 200 Generation Z respondents selected through purposive sampling. The participants were active social media users who had been exposed to body care product promotions delivered by local influencers. Data were gathered through a structured questionnaire and analyzed using descriptive statistics, validity and reliability tests, simple linear regression, t-tests, and coefficient of determination (R²) analysis with the support of SPSS software. The results show that local influencers generally employ effective content strategies characterized by relevance, creativity, consistency, high-quality information, and strong audience engagement. The findings also indicate that respondents exhibit a moderate level of brand awareness toward body care products promoted through social media. More importantly, the regression analysis demonstrates that influencers’ content strategies have a positive and statistically significant effect on brand awareness. This suggests that well-designed and engaging content plays a crucial role in enhancing consumers’ ability to recognize, recall, and differentiate brands. The study contributes to the growing body of digital marketing literature by providing empirical evidence on the effectiveness of local influencer marketing in shaping brand awareness among Generation Z consumers. The findings offer practical insights for marketers and business owners seeking to strengthen brand positioning and consumer engagement through strategic influencer-driven content on social media platforms.